Aspects of the study of kazakh mythology (Eurasian Journal of Philology Science and Education, 2018)
The article deals with the origins of Kazakh mythology, including the stages of its scientific study.This article describes the similarities and differences between different approaches to the mythologicalmaterial. Comparison of various aspects of theoretical mythology is traditionally considered one of themost effective methods of modern schools of mythology. Interest in myth at the present stage is alreadycharacterized by a broad interdisciplinary approach. Mythology has become the focus of importanthuman problems, profound philosophical generalizations. Science threw a bridge between myth andmodernity. Mythological subjects and forms play an important role in the texts of many contemporaryworks. Myths, legends and parables included in the work often fulfill a structuring role. Myth-makingand mythopoetics have become a phenomenon that has accumulated a huge aesthetic and philosophicalpotential. The results of the conducted studies showed that the movement of mythopoetics is noticeablenot only in the quantitative increase in the number of writers who paid tribute to the myth, but also in aqualitative change in the functionality of the myth in literary works.